Penerapan Algoritma C4.5 Untuk Rekomendasi Bantuan Dana Orang Terlantar dalam Perjalanan (OTDP) di Dinas Sosial Kota Cirebon - Magdalena, Lena; Oktaviani, Priti; Septiani, Willy Eka (Journal Cerita: Creative Education of Research in Information Technology and Artificial Informatics, 2024)
The C4.5 algorithm is a machine learning method based on decision trees, which has the ability to predict categories based on attributes present in the data. This research aims to address issues by implementing the C4.5 algorithm in forming a recommendation system for providing financial assistance to Homeless People during Travel (OTDP) in the Social Service of Cirebon City. This research process involves three main stages. First, data collection is carried out regarding OTDP who have received financial assistance previously, as well as related attributes such as age, address, travel purpose, and occupation. The second stage involves data processing to clean and reorganize the dataset to fit the C4.5 Algorithm format. Finally, it is applied to form a prediction that will provide recommendations for financial assistance to OTDP. OTDP is a vulnerable group that often requires social assistance from the government. In Cirebon City, the Social Service is responsible for providing financial assistance to support their travel. However, determining the right recipients for assistance is a challenge because the number of OTDP in need of assistance can vary over time. Therefore, it is hoped that the results of this research will provide a more efficient and accurate recommendation system in determining financial assistance recipients for OTDP, with a focus on the "Short Distance" category with a grant amount of "Rp120,000" and "Long Distance" with a grant amount of "Rp150,000". With this recommendation system, it is expected that the Social Service of Cirebon City can become more responsive in providing assistance to OTDP groups in need.